The effect of pre-deposited titanium-based PVD metallic thin films on the nitrogen diffusion efficiency and wear behaviour of nitrided Ti alloys - YUMUŞAK, GÖRKEM (ELSEVIER SCIENCE SA, 2020)
Low-temperature Triode Plasma Nitriding (TPN) has been reported to increase the load-bearing capacity of titanium alloys without compromising either core strength or fatigue resistance. It is known also that the effective adhesion between PVD hard coatings and titanium alloy substrates can be improved significantly following substrate diffusion pre-treatment. In TPN treatment the diffusion of the nitrogen can be achieved more efficiently (than conventional nitriding techniques) at a comparatively low substrate temperature and after relatively short treatment times. Moreover, there is evidence to suggest that the effectiveness of the triode-plasma diffusion treatment can be further increased by depositing a suitable thin PVD metallic layer on to the titanium alloy substrate before plasma nitriding treatment, to beneficially modify the diffusion kinetics. In this paper, both hcp-alpha and bcc-beta titanium coatings (the latter stabilised by the addition of Nb) are applied to (alpha + beta) Ti-6Al-4V and (beta) Ti-4Al-10V-22Mo substrate materials; the effects of a Ti and beta Ti-Nb PVD pre-coating on the diffusion treatment efficiency (and nitride phase development) and the wear behaviour of each of the Ti alloy substrates after TPN treatment at 700 degrees C is evaluated.
Keywords: Titanium-niobium coatings; Magnetron sputtering; Triode plasma nitriding; Micro-abrasion test; TI-6AL-4V ALLOY; PLASMA; COATINGS; MICROSTRUCTURE; PERFORMANCE; MORPHOLOGY